Mechanical properties of the new generation RACE EVO and r-motion nickel-titanium instruments - Baştürk, Fatıma Betül; Özyürek, Taha; Uslu, Gülşah; Gündoğar, Mustafa (MDPI, 2022)
This study aimed to evaluate and compare the dynamic cyclic fatigue, torsional and bending resistance of two novel RACE EVO (FKG Dentaire SA, La Chaux de Fonds, Switzerland) and R-Motion (FKG) nickel-titanium instruments with traditional RaCe (FKG) instruments. RACE EVO, R-Motion and RaCe instruments with a size of 25 and taper of 0.06 were used. A dynamic cyclic fatigue test was used to assess the time to fracture. The fractured surfaces were further analyzed using scanning electron microscopy at x350 and x3000 magnifications. A torsional resistance test was performed to measure the maximum torsional strength and angle of rotation. Phase transformations with temperature were evaluated using differential scanning calorimetry. The results were statistically analyzed with a Kruskal-Wallis test at a 5% significance level. R-Motion had the highest time to fracture and the lowest torsional and bending resistance, whereas RaCe had the lowest time to fracture and the highest torsional and bending resistance (p < 0.05). In relation to the angle of rotation, RACE EVO instruments had the highest deformation capacity followed by R-Motion and RaCe instruments (p < 0.05). The greater cyclic fatigue resistance and lower torsional and bending resistance results indicate that the novel R-Motion and RACE EVO instruments are less rigid and more flexible than RaCe instruments.
Keywords: Bending Resistance; Dynamic Cyclic Fatigue Resistance; Differential Scanning Calorimetry; Reciprocation; Torsion